Father-child relationship as moderator of the relationship between perceived paternal parenting style and self-reported delinquency among Filipino adolescents. - Mata, Mikha Jane Dalipe
The present study is designed to examine Father-Child Relationship as Moderator between the Relationship of Perceived Paternal Parenting Style and Self-Reported Delinquency. Non-experimental design in the form of survey was conducted among 73 high school students from Guimbal National High School. The data were analyzed using Regression Analysis. The results show that perceived paternal parenting style and father-child relationship as significant predictors of self-reported delinquency. Multiple Regression Analysis revealed that authoritarian and permissive parenting style significantly predicted self-reported delinquency. However, moderation analysis showed that father-child relationship did not moderate the relationship between perceived paternal parenting style and self-reported delinquency. Nevertheless, the study illustrates the importance of fathers' involvement as an important factor in influencing adolescents' behaviors.